Negotiating Isra’iliyyat in Modern Indonesian Tafsir : A Comparative Study of Hamka and Quraish Shihab on the Story of Harut and Marut (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2025)
This study is motivated by the enduring presence of Isrā’īliyyāt narratives in several modern Indonesian tafsīr works, despite the reformist movement’s emphasis on purifying Qur’anic exegesis from unreliable reports and upholding principles of textual authenticity and rational reasoning. Although the rejection of Isrā’īliyyāt has become a defining feature of reformist exegetical discourse, many modern mufassirs continue to incorporate these narrative elements with varying forms and degrees of acceptance. The story of Hārūt and Mārūt in QS. al-Baqarah:102 serves as a prominent example, as it frequently provokes debate regarding the reliability of its reports, its theological implications, and its connection to Jewish–Christian traditions that have influenced certain strands of Muslim exegesis.This article examines how Hamka and M. Quraish Shihab interpret and reason about this narrative in Tafsir al-Azhar and Tafsir al-Misbāḥ. This study employs a qualitative library-based approach with descriptive–comparative analysis, using the framework of Isrā’īliyyāt criticism and theories of traditional narrative reception in modern tafsīr. The findings show that Hamka adopts a highly selective stance and largely rejects Isrā’īliyyāt elements, whereas Quraish Shihab is more accommodating while maintaining caution. These differences highlight the epistemological diversity within modern Indonesian exegesis. The study contributes to Qur’anic hermeneutics in Southeast Asia by illustrating how classical narrative heritage is negotiated alongside modern rationalist demands and contemporary cultural contexts. Penelitian ini dilatarbelakangi oleh masih kuatnya keberadaan narasi Isrā’īliyyāt dalam sebagian tafsir modern Indonesia, meskipun arus utama reformisme menekankan penyucian tafsir dari riwayat yang tidak valid serta pentingnya kemurnian sumber dan rasionalitas. Penolakan terhadap Isrā’īliyyāt memang menjadi ciri utama wacana reformasi tafsir, namun faktanya sejumlah mufasir modern tetap memuat unsur-unsur naratif tersebut dengan cara dan tingkat penerimaan yang beragam. Kisah Hārūt dan Mārūt dalam QS. al-Baqarah:102 menjadi contoh yang menonjol karena sering memunculkan perdebatan, baik tentang keaslian riwayatnya, dampak teologis yang ditimbulkannya, maupun kaitannya dengan tradisi Yahudi-Kristen yang turut mempengaruhi sebagian penafsiran Muslim. Artikel ini menelusuri bagaimana Hamka dan M. Quraish Shihab memahami serta menalar kisah tersebut melalui Tafsir al-Azhar dan Tafsir al-Misbāḥ. Penelitian menggunakan metode kualitatif berbasis studi pustaka dengan analisis deskriptif–komparatif, menggunakan kerangka kritik Isrā’īliyyāt dan teori penerimaan narasi tradisional dalam tafsir modern. Hasilnya menunjukkan bahwa Hamka bersikap sangat selektif dan cenderung menolak unsur Isrā’īliyyāt, sedangkan Quraish Shihab lebih terbuka namun tetap berhati-hati. Perbedaan keduanya menegaskan adanya keragaman epistemologis dalam tafsir modern Indonesia. Temuan ini turut memperkaya kajian hermeneutika al-Qur’an di Asia Tenggara, terutama dalam melihat bagaimana warisan klasik dinegosiasikan dengan tuntutan rasionalitas dan konteks budaya masa kini.